2014
DOI: 10.1186/1478-4491-12-27
|View full text |Cite
|
Sign up to set email alerts
|

Positive practice environments influence job satisfaction of primary health care clinic nursing managers in two South African provinces

Abstract: BackgroundNurses constitute the majority of the health workforce in South Africa and they play a major role in providing primary health care (PHC) services. Job satisfaction influences nurse retention and successful implementation of health system reforms. This study was conducted in light of renewed government commitment to reforms at the PHC level, and to contribute to the development of solutions to the challenges faced by the South African nursing workforce. The objective of the study was to determine over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
86
3
15

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(118 citation statements)
references
References 52 publications
(66 reference statements)
14
86
3
15
Order By: Relevance
“…These positive factors however did not influence and determine job choices among our participants. This supports the findings of other researchers that state that despite the challenges faced working in a rural district hospital, there can still be high levels of job satisfaction (Hegney & McCarthy, 2000;Munyewende et al, 2014). In addition, our findings suggest health workers in rural areas were much more likely to be living away from their families (partner/spouse and children) and in hospital accommodation, a situation which frequently led to dissatisfaction and a desire to leave their current post which correlates to findings of Steinmetz et al (2014) who found having children at home increases turnover of nurses.…”
Section: Discussionsupporting
confidence: 80%
“…These positive factors however did not influence and determine job choices among our participants. This supports the findings of other researchers that state that despite the challenges faced working in a rural district hospital, there can still be high levels of job satisfaction (Hegney & McCarthy, 2000;Munyewende et al, 2014). In addition, our findings suggest health workers in rural areas were much more likely to be living away from their families (partner/spouse and children) and in hospital accommodation, a situation which frequently led to dissatisfaction and a desire to leave their current post which correlates to findings of Steinmetz et al (2014) who found having children at home increases turnover of nurses.…”
Section: Discussionsupporting
confidence: 80%
“…Thus, mental health services must combine physical resources with the work demands in order to decrease the work overloads to the health of nursing staff, (4) since organizational aspects may play a more significant role for the professional burnout than individual aspects. (1,9) The heavy working hours and multiple functions have also been mentioned as physical loads to which nursing professionals were exposed, consisting work overload and generating negative impacts on the workers' health.…”
Section: Discussionmentioning
confidence: 99%
“…(13,14) Moreover, the construction of a pleasant atmosphere in the workplace contributes to the prevention of professionals' emotional exhaustion. (1) Many nursing workers identify themselves with the professional activity they develop, but feel with few internal resources to cope better with unexpected situations that arise in the daily service, such as a discussion between users starting unexpectedly or aggressive actions of users with other professionals or themselves. For not knowing how to handle these demands, the physical and/or mental loads are more perceived.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In competitive global health care settings, there is recognition of the importance of the health workforce to health systems development, and the need to establish a positive work climate is increasingly critical to nurses' satisfaction, productivity, and performance [1]. A positive organizational climate can increase nurses' commitment to their job and reduce their intention to leave [2].…”
Section: Introductionmentioning
confidence: 99%